Pengaruh Komunikasi Persuasif Guru terhadap Motivasi Belajar Siswa Saat Pandemi COVID-19 - Nathania Juliani Christy; Roswita Oktavianti (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Communication between teachers and students is an important aspect in learning process, especially during the COVID-19 Pandemic. The learning process, which usually happens face-to-face in schools, is suddenly forced to shift to online learning at home to prevent the spread of the virus. This study aims to determine whether there is an effect of teacher’s persuasive communication on student’s learning motivation during online learning and how much influence it has. This study uses the theory of persuasive communication principles and the theory of sources of motivation. The researcher uses quantitative method with a survey using 5-level Likert scale questionnaire. The population of this study is students of Methodist Banda Aceh junior high school with a sample of 112 respondents using simple random sampling technique. Based on the results of research, teacher’s persuasive communication does effect on student’s learning motivation during online learning. It was found that the student's learning motivation was influenced about 67.6% by the teacher's persuasive communication, while the remaining 32.4% was influenced by other variables that are not examined in this study.Komunikasi antara guru dan siswa merupakan aspek penting dalam pembelajaran khususnya saat pandemi COVID-19. Proses belajar yang biasanya terjadi secara tatap muka di sekolah, secara mendadak dipaksa beralih ke pembelajaran secara daring untuk mencegah penyebaran virus corona. Penelitian ini ingin mengetahui apakah ada pengaruh komunikasi persuasif guru terhadap motivasi belajar siswa selama pembelajaran daring serta seberapa besar pengaruh tersebut. Peneliti menggunakan pendekatan kuantitatif dengan metode survei menggunakan kuesioner online. Populasi dari penelitian ini adalah siswa/i SMP Methodist Banda Aceh dengan sampel yang diambil sebanyak 112 responden dan menggunakan teknik simple random sampling. Dari penelitian ini ditemukan bahwa ditemukan ada pengaruh komunikasi persuasif guru terhadap motivasi belajar siswa selama pembelajaran daring. Pengaruh tersebut sebesar 67,6%, sementara sisanya 32,4% dipengaruhi oleh variabel- variabel lain.